A note on Argentina, Its crisis and the theory of Exchange Rate Determination - Féliz, Mariano (2007)
Argentina's crisis at the end of the twentieth century surprised economists. Argentina turned from a "Latin American miracle" to an unprecedented failure. This article looks into the crisis stressing the role of the exchange rate regime and emphasizes the overvaluation of the real exchange rate as a part of capital?s strategy to decompose labor and restructure capital-labor relations. Argentina's crisis resulted from the combination of capital's strategic success and the recomposition of labor in the late nineties